Service provision and quality outcomes in home health for rural Medicare beneficiaries at high risk for unplanned care. Issue 3 (3rd July 2018) - Mroz, Tracy M.; Andrilla, C. Holly A.; Garberson, Lisa A.; Skillman, Susan M.; Patterson, Davis G.; Larson, Eric H.
ABSTRACT: Multiple barriers exist to providing home health care in rural areas. This study examined relationships between service provision and quality outcomes among rural, fee-for-service Medicare beneficiaries who received home health care between 2011 and 2013 for conditions associated with high-risk for unplanned care. More skilled nursing visits, visits by more types of providers, more timely care, and shorter lengths of stay were associated with significantly higher odds of hospital readmission and emergency department use and significantly lower odds of community discharge. Results may indicate unmeasured clinical severity and care needs among this population. Additional research regarding the accuracy of current severity measures and adequacy of case-mix adjustment for quality metrics is warranted, especially given the continued focus on value-based payment policies.